Preparation method of high-selectivity heat-stable polyimide helium separation membrane
Patent Information
- Application Number
- CN202611233334.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]本发明针对现有技术中聚酰亚胺氦气分离膜难以同时兼顾高通量、高选择性与高热稳定性,填料易团聚、填料-基体界面相容性差,氟化改性不均导致膜性能衰减快的缺陷,本发明提供一种高选择性热稳定的聚酰亚胺氦气分离膜的制备方法,通过制备含固有纳米片层结构的二维氮化碳纳米片作为填料,结合梯度气相氟化改性工艺,可同步提升膜的氦气分离选择性与热稳定性,适配工业提氦的长期运行要求
(1)本发明采用卤代咪唑类离子液体与碳酸氢铵协同制备二维多孔氮化碳纳米片,二者协同实现薄层化剥离与孔结构精准调控:碳酸氢铵在升温初期受热分解,释放气体使前驱体形成蓬松多孔的预聚体,有效抑制热缩聚过程中的颗粒团聚与层间堆叠,配合后续超声分散与离心分级,可高效得到厚度均一的薄层纳米片;卤代咪唑类离子液体作为软模板,在热缩聚过程中原位诱导形成面内纳米孔道,其分解产生的含氮中间体可参与缩聚过程,进一步调控孔道尺寸与表面化学性质。所得二维氮化碳纳米片的面内孔道尺寸与氦气分子动力学直径适配,可作为氦气的优先快速传输通道,有效提升渗透通量;同时二维片层在聚酰亚胺基体中均匀分散,可构建曲折扩散路径,阻碍氮气、甲烷等大分子杂质的渗透,强化分子筛分效果。二者协同作用下,同时实现氦气通量与分离选择性的双向提升,改善了传统填料 “通量提升则选择性下降” 的固有矛盾。
Smart Images

Figure CN122998985A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of separation membrane technology, specifically relating to a method for preparing a highly selective, thermally stable polyimide-helium gas separation membrane. Background Technology
[0002] Helium is a scarce strategic resource, widely used in high-end fields such as semiconductor manufacturing, aerospace, cryogenic superconductivity, and medical MRI. China's helium supply is highly dependent on imports. Currently, large-scale industrial helium extraction methods mainly fall into three categories: cryogenic separation equipment requires large investments and consumes high energy; pressure swing adsorption (PSA) molecular sieves have limited adsorption capacity, and their adsorption performance rapidly declines under high-temperature conditions; membrane separation technology involves no phase change, has compact equipment, and low operating costs, making it the preferred route for low-cost helium extraction under high-temperature conditions.
[0003] Polyimide (PI) is one of the most widely used commercial gas separation membrane materials due to its excellent mechanical strength, thermochemical stability, and film-forming processability. However, pure polyimide membranes are limited by the "Robeson upper limit," where gas permeation flux and separation selectivity are inversely related, making it difficult to simultaneously meet the industrial demands for high flux and high selectivity.
[0004] Hybrid matrix membranes, by introducing nanofillers into a polymer matrix, combine the molecular sieving effect of the fillers with the film-forming advantages of the polymer, representing a mainstream technological approach to breaking through performance limits. Existing technologies mostly use molecular sieve particles, MOF particles, and carbon nanotubes as fillers. However, three-dimensional particle fillers are prone to agglomeration in polymers and have poor interfacial compatibility with polyimide matrices, easily generating interfacial voids and non-selective leakage, which in turn leads to a decrease in separation selectivity. Although ordinary two-dimensional nanomaterials (such as graphene oxide) can construct tortuous diffusion paths, they lack regular inherent channels, making it difficult to achieve precise molecular sieving of impurities such as helium, nitrogen, and methane, resulting in limited improvement in selectivity.
[0005] Fluorination modification is a common method for controlling the free volume of polyimide and optimizing gas separation performance. However, existing processes often employ one-step high-temperature fluorination or high-concentration fluorination, which has significant drawbacks: First, the fluorination reaction is concentrated on the membrane surface, easily leading to excessive surface fluorination, membrane embrittlement and cracking, and decreased mechanical properties; second, the degree of fluorination is unevenly distributed along the membrane thickness, resulting in insufficient modification of the internal matrix and difficulty in simultaneously improving separation performance and thermal stability; third, conventional fluorination cannot improve the interfacial bonding force between the packing material and the matrix, and may even exacerbate interfacial delamination, causing the membrane to degrade rapidly under high temperature and long-term operation, making it unsuitable for the harsh conditions of industrial-grade helium recovery.
[0006] Therefore, developing a method for preparing polyimide separation membranes that combines high helium selectivity, high thermal stability, and long-term operational stability is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] This invention addresses the shortcomings of existing polyimide helium separation membranes, which struggle to simultaneously achieve high throughput, high selectivity, and high thermal stability. These shortcomings include filler agglomeration, poor filler-matrix interface compatibility, and rapid performance degradation due to uneven fluorination modification. The invention provides a method for preparing a highly selective and thermally stable polyimide helium separation membrane. By preparing two-dimensional carbon nitride nanosheets with an inherent nanosheet structure as filler, combined with a gradient gas-phase fluorination modification process, the helium separation selectivity and thermal stability of the membrane can be simultaneously improved, meeting the long-term operational requirements of industrial helium extraction.
[0008] The objective of this invention is achieved through the following technical solution: The highly selective thermally stable polyimide helium separation membrane of this invention uses porous two-dimensional carbon nitride nanosheets prepared by ionic liquid-ammonium bicarbonate synergy as filler. After being blended with hexafluorodianhydride-type polyimide to form a membrane, it undergoes a three-step gradient gas-phase fluorination treatment to obtain: the sub-nanometer-scale channels distributed within the carbon nitride nanosheets are adapted to the size of helium molecules, providing preferential helium transport channels; the two-dimensional sheet structure can extend the diffusion path of impurity molecules; ionic liquid-assisted thermal polycondensation can regulate the polar functional groups on the surface of carbon nitride, improve the interfacial compatibility between the filler and the polyimide matrix, and eliminate non-selective leakage at the interface; gradient gas-phase fluorination gradually regulates the degree of fluorination from the membrane surface to the interior, avoiding excessive surface fluorination and degradation, while optimizing the free volume distribution of the polyimide matrix, further improving the helium permeation performance and separation selectivity, and simultaneously enhancing the overall thermal stability of the membrane.
[0009] To achieve the above-mentioned technical objectives, the specific technical solution adopted by this invention is as follows: A method for preparing a highly selective, thermally stable polyimide helium gas separation membrane includes the following preparation steps: (1) Filler preparation: Two-dimensional carbon nitride nanosheets with nanoporous structures were prepared as porous fillers for the mixed matrix membrane; (2) Preparation of casting solution: Polyimide resin is dissolved in an organic solvent to obtain a homogeneous polyimide casting solution; the two-dimensional porous nanosheet filler is dispersed in an organic solvent to obtain a homogeneous filler dispersion; the filler dispersion and polyimide casting solution are mixed and stirred, and vacuum degassed to obtain a mixed casting solution; (3) Preparation of primary membrane: The mixed casting solution is coated onto the surface of the support, the solvent is evaporated by heating and vacuum dried to obtain a primary polyimide mixed matrix membrane; (4) Gradient gas phase fluorination treatment: The nascent mixed matrix membrane is placed in a gas phase fluorination reactor and treated using a three-step gradient fluorination process. After treatment, it is purged with inert gas and cooled to obtain the polyimide helium separation membrane.
[0010] Preferably, the preparation method of two-dimensional carbon nitride nanosheets with a nanoporous structure is as follows: a nitrogen-containing precursor, a halogenated 1-alkyl-3-methylimidazolium ionic liquid porogen, and ammonium bicarbonate are mixed uniformly in a mass ratio of 1:(0.05~0.5):(0.1~1.0). Under an inert atmosphere, the mixture is first heated to 350~400℃ at a rate of 1~5℃ / min and held for 1~3 hours, then heated to 500~580℃ at the same rate and held for 2~5 hours for programmed temperature-controlled thermal polycondensation. The ammonium bicarbonate decomposes at low temperature to release gas, causing the precursor to form a fluffy and porous prepolymer, thus inhibiting excessive thermal polycondensation. The particle agglomeration during the process is beneficial for subsequent ultrasonic exfoliation to obtain thin nanosheets. The ionic liquid, as a soft template, forms in-situ in-plane nanopores during the thermal polycondensation process. At the same time, the nitrogen-containing intermediates decomposed by the ionic liquid participate in the polycondensation, regulating the surface polarity and functional group distribution of carbon nitride and enhancing the interfacial interaction with the polyimide matrix. Finally, porous carbon nitride nanosheet aggregates are obtained. The aggregates are dispersed in deionized water or ethanol, and after ultrasonic treatment or high-speed shear dispersion, they are centrifuged and graded. The upper suspension is dried to obtain two-dimensional nanosheets with a thickness of 1-20 nm and nanopores with a diameter of 0.3-0.5 nm distributed in the sheet.
[0011] More preferably, the nitrogen-containing precursor is one or more of melamine, urea, or dicyandiamide, and the halogenated 1-alkyl-3-methylimidazolium ionic liquid porogen is 1-butyl-3-methylimidazolium chloride or 1-butyl-3-methylimidazolium bromide.
[0012] Preferably, the amount of the two-dimensional porous nanosheet filler added in step (2) is 1~10wt% of the mass of the polyimide resin; the polyimide is a hexafluorodianhydride type polyimide, selected from 6FDA-ODA or 6FDA-mPDA; 6FDA-ODA or 6FDA-mPDA can be a commercially available finished product or can be self-made, and the self-made method is as follows: 6FDA-ODA polyimide: Hexafluorodianhydride (6FDA) and 4,4'-diaminodiphenyl ether (ODA) were vacuum dried to remove water, and then added to dehydrated N,N-dimethylacetamide in a molar ratio of 1:1. The solid content of the system was controlled at 10-15 wt%. The reaction was carried out under nitrogen protection and at 0-5°C for 6-8 h to obtain a polyamic acid solution. Acetic anhydride and triethylamine (molar ratio of acetic anhydride to diamine 2.5:1, molar ratio of triethylamine to diamine 1:1) were added, and the mixture was heated to 60°C for 3-4 h to complete imidization. The reaction solution was precipitated with anhydrous ethanol, washed, and vacuum dried to obtain 6FDA-ODA polyimide solid powder.
[0013] 6FDA-mPDA polyimide: Hexafluorodianhydride (6FDA) and m-phenylenediamine (mPDA) were vacuum dried to remove water, and then added to dehydrated N,N-dimethylacetamide in a molar ratio of 1:1. The solid content of the system was controlled at 10-15 wt%. The reaction was carried out under nitrogen protection and at 0-5℃ for 5-7 h to obtain a polyamic acid solution. Acetic anhydride and triethylamine (molar ratio of acetic anhydride to diamine 2.5:1, molar ratio of triethylamine to diamine 1:1) were added, and the temperature was raised to 60℃ for 3-4 h to complete imidization. The reaction solution was precipitated with anhydrous ethanol, washed, and vacuum dried to obtain 6FDA-mPDA polyimide solid powder.
[0014] The organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; the mass concentration of polyimide resin in the polyimide casting solution is 10~20wt%.
[0015] Preferably, the mass volume concentration of the homogeneous filler dispersion in step (2) is 1~10 mg / mL, and the dispersion solvent is the same as the organic solvent used in the polyimide casting solution.
[0016] Preferably, in step (3), the method for evaporating the solvent by heating is as follows: first, evaporate at atmospheric pressure at 40~60℃ for 4~8h, then heat to 80~100℃ for 2~4h, and finally heat to 120~160℃ for vacuum drying for 12~24h to completely remove the residual solvent; control the dry film thickness of the obtained nascent mixed matrix film to be 20~50μm.
[0017] Preferably, in step (4), the three-step gradient fluorination process is as follows: Step 1: low-concentration fluorination: the volume concentration of fluorine gas is 5~10 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 10~30 min; Step 2: medium-concentration fluorination: the volume concentration of fluorine gas is 15~25 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 20~40 min; Step 3: high-concentration fluorination: the volume concentration of fluorine gas is 30~40 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 30~60 min.
[0018] More preferably, the pressure inside the reactor during the entire fluorination process is 0.1~0.3MPa; after each fluorination step, the reaction gas is purged and high-purity nitrogen is introduced to purge the reactor for 10~20 minutes before proceeding to the next stage of fluorination; after all fluorination processes are completed, high-purity nitrogen is continuously introduced to purge until there is no fluorine residue in the tail gas, and the membrane material is removed after natural cooling to room temperature.
[0019] The present invention also provides a polyimide helium separation membrane prepared by the above method, which has high helium permeation flux, high He / N2 and He / CH4 separation selectivity, and excellent thermal stability and long-term operational stability.
[0020] Compared with the prior art, the beneficial effects of the present invention are reflected in the following aspects: (1) This invention uses haloimidazole ionic liquids and ammonium bicarbonate to synergistically prepare two-dimensional porous carbon nitride nanosheets. The two work together to achieve thin-layer exfoliation and precise control of pore structure: Ammonium bicarbonate decomposes upon heating in the early stage, releasing gas to form a fluffy and porous prepolymer of the precursor, effectively inhibiting particle agglomeration and interlayer stacking during thermal polycondensation. Combined with subsequent ultrasonic dispersion and centrifugal classification, thin nanosheets with uniform thickness can be obtained efficiently. The haloimidazole ionic liquid acts as a soft template, inducing the formation of in-plane nanopores in situ during thermal polycondensation. The nitrogen-containing intermediates produced by its decomposition can participate in the polycondensation process, further controlling the pore size and surface chemical properties. The in-plane pore size of the obtained two-dimensional carbon nitride nanosheets is adapted to the molecular dynamics diameter of helium, which can serve as a preferential fast transport channel for helium, effectively improving the permeation flux. At the same time, the two-dimensional sheets are uniformly dispersed in the polyimide matrix, which can construct a tortuous diffusion path, hindering the permeation of macromolecular impurities such as nitrogen and methane, and enhancing the molecular sieving effect. The synergistic effect of the two simultaneously improves both helium flux and separation selectivity, thus resolving the inherent contradiction of traditional packing materials where "increased flux leads to decreased selectivity".
[0021] (2) The present invention prepares carbon nitride filler by ionic liquid-assisted thermal polycondensation, which can introduce abundant nitrogen-containing polar functional groups on the surface of nanosheets. These functional groups can form hydrogen bonds and dipole-dipole interactions with the imide groups and aromatic ether structures of polyimide segments, significantly improving the interfacial compatibility between carbon nitride nanosheets and polyimide matrix, eliminating non-selective voids at the filler-matrix interface, and avoiding the decrease in separation selectivity caused by non-selective leakage. At the same time, the improved interfacial bonding force can effectively suppress the interfacial peeling between the filler and the matrix during high-temperature operation, greatly improving the long-term operational stability of the membrane and adapting to the high-temperature and long-cycle operation conditions of industrial helium extraction.
[0022] (3) This invention employs a three-step gradient gas-phase fluorination process, gradually modifying the membrane material from low to high concentrations to ensure uniform distribution of fluorination along the membrane thickness. This process offers significant advantages over the traditional one-step fluorination process: one-step low-concentration fluorination suffers from insufficient modification depth and inadequate control of free volume within the matrix, making it difficult to effectively improve separation selectivity; one-step high-concentration fluorination is prone to excessive reaction on the membrane surface, leading to excessive cross-linking of polymer segments and collapse of free volume, which in turn causes a simultaneous decrease in permeate flux and selectivity. The gradient fluorination process of this invention ensures that the polyimide matrix inside the membrane receives sufficient fluorination modification, allowing for precise control of polymer free volume distribution and increasing free volume sites for helium diffusion, further enhancing helium permeate flux and separation selectivity; it also avoids structural degradation caused by excessive surface fluorination, while significantly improving the thermochemical stability of the polyimide matrix and inhibiting membrane plasticization and performance degradation under high-temperature conditions.
[0023] (4) Two-dimensional carbon nitride nanosheets possess excellent heat resistance and mechanical reinforcement, which can inhibit high-temperature plasticization and chain segment relaxation of the polyimide matrix. Combined with the uniform and stable membrane structure formed by gradient fluorination, the synergistic effect of the two can effectively reduce the performance degradation rate under long-term high-temperature operation. After high-temperature long-term heat treatment and continuous mixed gas operation, the resulting separation membrane can maintain a high level of helium permeability and separation selectivity. Its performance stability is significantly better than that of conventional pure polyimide membranes and one-step fluorinated modified membranes, which can meet the long-term continuous operation requirements of industrial scenarios such as natural gas helium extraction, syngas helium recovery, and crude helium refining.
[0024] (5) The nitrogen-containing precursor, ionic liquid, polyimide resin and other raw materials used in this invention are all commercially available industrial products. The programmed temperature heating polycondensation, solution film scraping and gas phase fluorination are all mature industrial processes with a wide range of controllable parameters. No special customized equipment is required. It can be directly connected to the existing gas separation membrane production line for large-scale production and has good engineering application prospects. Attached Figure Description
[0025] Figure 1 This is a field emission scanning electron microscope image of the porous two-dimensional carbon nitride nanosheets prepared in Example 1 of the present invention; Figure 2 This is a schematic diagram of the gas-phase fluorination reaction apparatus used in this invention; Figure 3 The images show the morphological comparison of carbon nitride fillers obtained by different preparation processes using scanning electron microscopes. The bottom image shows the filler obtained in Comparative Example 2, and the top image shows the filler obtained in Comparative Example 3. Detailed Implementation
[0026] The technical solution of the present invention will be further described below with reference to specific embodiments, but it is not limited thereto.
[0027] Example 1 A method for preparing a highly selective, thermally stable polyimide helium gas separation membrane includes the following preparation steps: (1) Filler preparation: Two-dimensional carbon nitride nanosheets with nanoporous structure were prepared as porous fillers for the mixed matrix membrane; melamine, 1-butyl-3-methylimidazolium chloride and ammonium bicarbonate were mixed and ground evenly in a mass ratio of 1:0.25:0.5; under an inert argon atmosphere, the temperature was increased to 380℃ at a rate of 2℃ / min and held for 2h, and then increased to 550℃ at a rate of 2℃ / min and held for 3h for thermal condensation; the obtained carbon nitride aggregates were dispersed in ethanol, ultrasonically dispersed for 2h, centrifuged at 8000r / min for 10min, and the upper suspension was vacuum dried at 60℃ to obtain porous two-dimensional carbon nitride nanosheets.
[0028] (2) Preparation of casting solution: 6FDA-ODA polyimide was selected, and DMAC was used as the organic solvent; a 15wt% polyimide casting solution was prepared; the above carbon nitride nanosheets were dispersed in DMAC to prepare a 5mg / mL homogeneous filler dispersion; the filler addition amount was 5wt% of the 6FDA-ODA resin mass; the filler dispersion and polyimide casting solution were mixed and stirred for 12h, and vacuum degassing was performed for 2h to obtain a mixed casting solution. 6FDA-ODA was prepared using commercially available products or a self-made process. The self-made method is as follows: hexafluorodianhydride and 4,4'-diaminodiphenyl ether were added to dehydrated DMAC at a molar ratio of 1:1, the solid content of the system was 12wt%, and the mixture was stirred under nitrogen at 0~5℃ for 7h to prepare polyamic acid; acetic anhydride and triethylamine were added (acetic anhydride:diamine = 2.5:1, triethylamine:diamine = 1:1), and the mixture was reacted at 60℃ for 3.5h for imidization; ethanol precipitation and washing were performed, and the mixture was vacuum dried to obtain PI powder.
[0029] (3) Preparation of nascent membrane: The mixed casting solution was coated onto the surface of the polysulfone support; the heating program was as follows: first, it was evaporated at 50℃ under normal pressure for 6 hours, then the temperature was increased to 90℃ for 3 hours, and finally the temperature was increased to 140℃ for vacuum drying for 18 hours to completely remove residual solvent, thus obtaining the dry membrane of the nascent mixed matrix membrane. The thickness of the dry membrane of the obtained nascent mixed matrix membrane was controlled to be 30±2μm.
[0030] (4) Gradient gas phase fluorination treatment: Place the nascent membrane in Figure 2 The gas phase fluorination reactor operates at a gauge pressure of 0.2 MPa throughout the process and employs a three-step gradient fluorination process, with each stage ending with a 15-minute purging with high-purity nitrogen. Step 1: Low-concentration fluorination: Fluorine gas volume concentration 8 vol%, high-purity nitrogen as balance gas, treated at 80-90℃ for 20 min; purged for 15 min. The second step involves medium-concentration fluorination: fluorine gas volume concentration of 20 vol%, treated at 80-90℃ for 30 min; followed by purging for 15 min. The third step is high-concentration fluorination: fluorine gas volume concentration is 35 vol%, and the treatment is carried out at 80-90℃ for 45 min; after all fluorination processes are completed, high-purity nitrogen is continuously purged until there is no fluorine residue in the tail gas, and the gas is naturally cooled to room temperature to obtain the polyimide helium separation membrane of this embodiment.
[0031] Example 2 A method for preparing a highly selective, thermally stable polyimide helium gas separation membrane includes the following preparation steps: (1) Filler preparation: Two-dimensional carbon nitride nanosheets with nanoporous structure were prepared as porous fillers for the mixed matrix membrane. Melamine, 1-butyl-3-methylimidazolium chloride ionic liquid porogen and ammonium bicarbonate were mixed evenly in a mass ratio of 1:0.05:0.1. Under an inert argon atmosphere, the temperature was first raised to 350℃ at 1℃ / min and held for 1 hour, and then raised to 500℃ at 1℃ / min and held for 2 hours for programmed temperature rise thermal polycondensation. After the polycondensation was completed, the aggregates were dispersed in deionized water, ultrasonically dispersed for 1 hour, centrifuged at 6000r / min for 8 minutes, and the upper suspension was vacuum dried at 50℃ to obtain two-dimensional carbon nitride nanosheets.
[0032] (2) Preparation of casting solution: 6FDA-ODA type polyimide was selected, and N,N-dimethylformamide (DMF) was used as the organic solvent. The 6FDA-ODA polyimide resin was dissolved in DMF to prepare a homogeneous polyimide casting solution with a mass concentration of 10wt%. The above two-dimensional porous carbon nitride nanosheet filler was dispersed in DMF to prepare a homogeneous filler dispersion with a concentration of 1mg / mL. The amount of two-dimensional porous nanosheet filler added was 1wt% of the mass of polyimide resin. The filler dispersion and polyimide casting solution were mixed and stirred for 8h and vacuum degassed for 1h to obtain a mixed casting solution. 6FDA-ODA can be obtained using commercially available products or a self-made process. The self-made method is as follows: Hexafluorodianhydride (6FDA) and 4,4'-diaminodiphenyl ether (ODA) are vacuum dried to remove water, and then added to dehydrated DMF in a molar ratio of 1:1, controlling the solid content of the system to be 10wt%. The reaction is carried out under nitrogen protection and at 0~5℃ for 6h with stirring to obtain a polyamic acid solution. Acetic anhydride and triethylamine are added (the molar ratio of acetic anhydride to diamine is 2.5:1, and the molar ratio of triethylamine to diamine is 1:1), and the temperature is raised to 60℃ for 3h to complete imidization. The reaction solution is precipitated with anhydrous ethanol, washed, and vacuum dried to obtain 6FDA-ODA polyimide solid powder.
[0033] (3) Preparation of nascent membrane: The mixed casting solution was coated onto the surface of the polysulfone support. The solvent was evaporated using a segmented heating program and then vacuum dried: first, it was evaporated at 40℃ under normal pressure for 4 hours, then heated to 80℃ for 2 hours, and finally heated to 120℃ for vacuum drying for 12 hours to completely remove residual solvent, thus obtaining the dry membrane of the nascent mixed matrix membrane. The thickness of the obtained dry membrane of the nascent mixed matrix membrane was controlled to be 30±2μm.
[0034] (4) Gradient gas-phase fluorination treatment: The nascent mixed matrix membrane is placed in an adjacent... Figure 2 In the gas phase fluorination reactor, the pressure inside the reactor is 0.1 MPa throughout the fluorination process. A three-step gradient fluorination process is adopted. After each fluorination step is completed, the reaction gas is vented and high-purity nitrogen is introduced to purge the reactor for 10 minutes before proceeding to the next stage of fluorination. Step 1: Low-concentration fluorination: Fluorine gas volume concentration is 5 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 10 min. The second step is medium-concentration fluorination: the volume concentration of fluorine gas is 15 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 20 min. The third step is high-concentration fluorination: the volume concentration of fluorine gas is 30 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 30 min; after all fluorination processes are completed, high-purity nitrogen is continuously introduced to purge until there is no fluorine gas residue in the tail gas, and the membrane material is taken out after natural cooling to room temperature to obtain the polyimide helium separation membrane of this embodiment.
[0035] Example 3 A method for preparing a highly selective, thermally stable polyimide helium gas separation membrane includes the following preparation steps: (1) Filler preparation: Two-dimensional carbon nitride nanosheets with nanoporous structure were prepared as porous fillers for the mixed matrix membrane. Dicyandiamide, 1-butyl-3-methylimidazolium bromide ionic liquid porogen and ammonium bicarbonate were mixed evenly in a mass ratio of 1:0.5:1.0. Under an inert argon atmosphere, the temperature was first raised to 400℃ at 5℃ / min and held for 3 hours, and then raised to 580℃ at 5℃ / min and held for 5 hours for programmed temperature rise thermal polycondensation. After the polycondensation was completed, the aggregates were dispersed in ethanol, ultrasonically dispersed for 3 hours, centrifuged at 10000r / min for 15 minutes, and the upper suspension was vacuum dried at 70℃ to obtain two-dimensional carbon nitride nanosheets.
[0036] (2) Preparation of casting solution: 6FDA-mPDA type polyimide was selected, and N-methylpyrrolidone (NMP) was used as the organic solvent; 6FDA-mPDA polyimide resin was dissolved in NMP to prepare a homogeneous polyimide casting solution with a mass concentration of 20wt%; the above two-dimensional porous carbon nitride nanosheet filler was dispersed in NMP to prepare a homogeneous filler dispersion of 10mg / mL; the amount of two-dimensional porous nanosheet filler added was 10wt% of the mass of polyimide resin; the filler dispersion and polyimide casting solution were mixed and stirred for 16h and vacuum degassed for 3h to obtain a mixed casting solution. 6FDA-mPDA can be obtained using commercially available products or a self-made process. The self-made method is as follows: Hexafluorodianhydride (6FDA) and m-phenylenediamine (mPDA) are vacuum dried to remove water, and then added to dehydrated NMP at a molar ratio of 1:1, controlling the solid content of the system to be 15wt%. The reaction is carried out under nitrogen protection and at 0~5℃ for 7h to obtain a polyamic acid solution. Acetic anhydride and triethylamine (the molar ratio of acetic anhydride to diamine is 2.5:1, and the molar ratio of triethylamine to diamine is 1:1) are added, and the temperature is raised to 60℃ for 4h to complete imidization. The reaction solution is precipitated with anhydrous ethanol, washed, and vacuum dried to obtain 6FDA-mPDA polyimide solid powder.
[0037] (3) Preparation of nascent membrane: The mixed casting solution was coated onto the surface of the polysulfone support. The solvent was evaporated using a segmented heating program and then vacuum dried: first, it was evaporated at 60℃ under normal pressure for 8 hours, then heated to 100℃ for 4 hours, and finally heated to 160℃ for vacuum drying for 24 hours to completely remove residual solvent, thus obtaining the dry membrane of the nascent mixed matrix membrane. The thickness of the obtained dry membrane of the nascent mixed matrix membrane was controlled to be 30±2μm.
[0038] (4) Gradient gas-phase fluorination treatment: The nascent mixed matrix membrane is placed in an adjacent... Figure 2 In the gas phase fluorination reactor, the pressure inside the reactor is 0.3 MPa throughout the fluorination process. A three-step gradient fluorination process is adopted. After each fluorination step is completed, the reaction gas is vented and high-purity nitrogen is introduced to purge the reactor for 20 minutes before entering the next stage of fluorination. Step 1: Low-concentration fluorination: Fluorine gas volume concentration is 10 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 30 min. The second step is medium-concentration fluorination: the volume concentration of fluorine gas is 25 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 40 min. The third step is high-concentration fluorination: the volume concentration of fluorine gas is 40 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 60 min; after all fluorination processes are completed, high-purity nitrogen is continuously introduced to purge until there is no fluorine gas residue in the tail gas, and the membrane material is taken out after natural cooling to room temperature to obtain the polyimide helium separation membrane of this embodiment.
[0039] Comparative Example 1 This comparative example omits the filler preparation process and does not add carbon nitride nanosheet filler; all other process steps are the same as in Example 1, i.e.: A method for preparing a polyimide helium separation membrane, comprising the following steps: (1) Filler preparation: The filler preparation process is omitted, and carbon nitride nanosheets are not synthesized.
[0040] (2) Preparation of casting solution: 6FDA-ODA polyimide was selected and DMAC was used as organic solvent to prepare 15wt% pure polyimide casting solution; there was no need to prepare filler dispersion, PI powder was directly dissolved in DMAC, stirred at room temperature for 12h, and vacuum degassed for 2h to obtain pure casting solution; the self-made process of 6FDA-ODA was the same as in Example 1.
[0041] (3) Preparation of primary membrane: The casting solution was coated onto the polysulfone support; solvent evaporation program: 50℃ atmospheric pressure for 6h → 90℃ atmospheric pressure for 3h → 140℃ vacuum for 18h. The dry membrane thickness of the obtained primary mixed matrix membrane was controlled to be 30±2μm.
[0042] (4) Gradient gas-phase fluorination treatment: Place the pure PI nascent membrane into the substrate. Figure 2 The fluorination reactor was maintained at a gauge pressure of 0.2 MPa throughout the process. The three-step fluorination concentration, temperature, time, nitrogen purging duration, and tail gas treatment process were completely consistent with those in Example 1. After cooling, a pure polyimide comparison membrane was obtained.
[0043] Comparative Example 2 In this comparative example, except that the halogenated 1-alkyl-3-methylimidazolium ionic liquid porogen (1-butyl-3-methylimidazolium chloride) was not used in the filler preparation, all other process steps were the same as in Example 1, namely: A method for preparing a polyimide helium separation membrane includes the following preparation steps: (1) Preparation of filler: Porous filler was prepared by mixing and grinding melamine and ammonium bicarbonate at a mass ratio of 1:0.5. Under an inert argon atmosphere, the temperature was increased to 380℃ at a rate of 2℃ / min and held for 2h. Then, the temperature was increased to 550℃ at a rate of 2℃ / min and held for 3h. The resulting carbon nitride aggregate was dispersed in ethanol, ultrasonically dispersed for 2h, centrifuged at 8000r / min for 10min, and the upper suspension was vacuum dried at 60℃ to obtain porous filler.
[0044] Step (2) Preparation of casting solution, Step (3) Preparation of primary membrane (the dry film thickness of the obtained primary mixed matrix membrane is controlled to be 30±2μm), and Step (4) Gradient gas phase fluorination treatment are all exactly the same as those in Example 1 in terms of raw materials, ratios, process parameters and operating procedures.
[0045] Comparative Example 3 In this comparative example, except that ammonium bicarbonate is not used in the preparation of the filler, all other process steps are the same as in Example 1, namely: A method for preparing a polyimide helium separation membrane includes the following preparation steps: (1) Preparation of filler: Porous filler was prepared by mixing and grinding melamine and 1-butyl-3-methylimidazole chloride at a mass ratio of 1:0.25. Under an inert argon atmosphere, the temperature was increased to 380℃ at a rate of 2℃ / min and held for 2h. Then, the temperature was increased to 550℃ at a rate of 2℃ / min and held for 3h for thermal polycondensation. The resulting carbon nitride aggregate was dispersed in ethanol, ultrasonically dispersed for 2h, centrifuged at 8000r / min for 10min, and the upper suspension was vacuum dried at 60℃ to obtain porous filler.
[0046] Step (2) Preparation of casting solution, Step (3) Preparation of primary membrane (the dry film thickness of the obtained primary mixed matrix membrane is controlled to be 30±2μm), and Step (4) Gradient gas phase fluorination treatment are all exactly the same as those in Example 1 in terms of raw materials, ratios, process parameters and operating procedures.
[0047] Comparative Example 4 In this comparative example, except that the halogenated 1-alkyl-3-methylimidazolium ionic liquid porogen (1-butyl-3-methylimidazolium chloride) and ammonium bicarbonate were not used in the filler preparation, all other process steps were the same as in Example 1, namely: A method for preparing a polyimide helium separation membrane, comprising the following steps: (1) Preparation of filler: Only melamine raw material is used, without adding 1-butyl-3-methylimidazole chloride or ammonium bicarbonate; under argon atmosphere, the temperature is raised to 380℃ at 2℃ / min and held for 2h, then raised to 550℃ and held for 3h for thermal polycondensation; the product is directly ground, dispersed in ethanol and sonicated for 2h, centrifuged at 8000r / min for 10min, and the upper suspension is dried at 60℃.
[0048] (2) Preparation of casting solution: Same as in Example 1, 15wt% 6FDA-ODA / DMAC casting solution, 5mg / mL filler dispersion, 5wt% filler addition, and stirring and degassing parameters remain unchanged.
[0049] (3) Preparation of primary membrane: The heating and drying procedure was exactly the same as in Example 1. The dry membrane thickness of the obtained primary mixed matrix membrane was controlled to be 30±2μm.
[0050] (4) Gradient gas phase fluorination treatment: All process parameters and purging procedures of the three-step gradient fluorination are exactly the same as those in Example 1.
[0051] Comparative Example 5 In this comparative example, except for the fluorination process, the raw materials for all other steps are the same as in Example 1, that is: A method for preparing a polyimide helium separation membrane, comprising the following steps: (1) Filler preparation: The raw material ratio, calcination, dispersion and drying parameters are completely consistent with those in Example 1.
[0052] (2) Preparation of casting solution: 6 FDA-ODA, DMAC solvent, and filler were added at 5 wt%, and the stirring and degassing parameters were all the same as in Example 1.
[0053] (3) Preparation of primary membrane: The solvent evaporation and vacuum drying procedures were the same as in Example 1. The dry membrane thickness of the obtained primary mixed matrix membrane was controlled to be 30±2μm.
[0054] (4) Vapor phase fluorination treatment: Place the primary membrane in Figure 2 The gas-phase fluorination reactor operates at a constant gauge pressure of 0.2 MPa, employing a one-step, single-concentration fluorination process. Low-concentration fluorination: Fluorine gas volume concentration of 8 vol%, high-purity nitrogen as the balance gas, treated at 80-90℃ for 95 min, after the fluorination process is completed, high-purity nitrogen is continuously purged until there is no fluorine residue in the tail gas, and then naturally cooled to room temperature to obtain a polyimide helium separation membrane.
[0055] Comparative Example 6 In this comparative example, except for the fluorination process, the raw materials for all other steps are the same as in Example 1, that is: A method for preparing a polyimide helium separation membrane, comprising the following steps: (1) Filler preparation: The raw material ratio, calcination, dispersion and drying parameters are completely consistent with those in Example 1.
[0056] (2) Preparation of casting solution: 6 FDA-ODA, DMAC solvent, and filler were added at 5 wt%, and the stirring and degassing parameters were all the same as in Example 1.
[0057] (3) Preparation of primary membrane: The solvent evaporation and vacuum drying procedures were the same as in Example 1. The dry membrane thickness of the obtained primary mixed matrix membrane was controlled to be 30±2μm.
[0058] (4) Vapor phase fluorination treatment: Place the primary membrane in Figure 2 The gas-phase fluorination reactor operates at a constant gauge pressure of 0.2 MPa, employing a one-step, single-concentration fluorination process. Medium-concentration fluorination: Fluorine gas volume concentration of 20 vol% is treated at 80-90℃ for 95 min. After the fluorination process is completed, high-purity nitrogen is continuously purged until there is no fluorine residue in the tail gas. The gas is then naturally cooled to room temperature to obtain a polyimide helium separation membrane.
[0059] Comparative Example 7 In this comparative example, except for the fluorination process, the raw materials for all other steps are the same as in Example 1, that is: A method for preparing a polyimide helium separation membrane, comprising the following steps: (1) Filler preparation: The raw material ratio, calcination, dispersion and drying parameters are completely consistent with those in Example 1.
[0060] (2) Preparation of casting solution: 6 FDA-ODA, DMAC solvent, and filler were added at 5 wt%, and the stirring and degassing parameters were all the same as in Example 1.
[0061] (3) Preparation of primary membrane: The solvent evaporation and vacuum drying procedures were the same as in Example 1. The dry membrane thickness of the obtained primary mixed matrix membrane was controlled to be 30±2μm.
[0062] (4) Vapor phase fluorination treatment: Place the primary membrane in Figure 2 The gas-phase fluorination reactor operates at a constant gauge pressure of 0.2 MPa, employing a one-step, single-concentration fluorination process. High-concentration fluorination: Fluorine gas volume concentration of 35 vol% is treated at 80-90℃ for 95 min. After the fluorination process is completed, high-purity nitrogen is continuously purged until there is no fluorine residue in the tail gas. The gas is then naturally cooled to room temperature to obtain a polyimide helium separation membrane.
[0063] Performance testing The separation membranes prepared in Examples 1-3 and Comparative Examples 1-7 were subjected to the following performance tests: Gas separation test: Gas separation performance was tested using a differential pressure gas permeation tester, and the test method followed the general specifications in this field (Reference: Design, synthesis and gas separation characteristics of polyimide gas separation membrane containing trimethylbenzene structure [J]. Membrane Science and Technology, 2025, 45 (4): 86-94.). The test temperature was 30℃, the upstream operating gauge pressure was 0.2MPa, and the sample was degassed under vacuum for 24h before the test.
[0064] The pure gas permeation fluxes of high-purity helium (He), nitrogen (N2), and methane (CH4) were measured, respectively, with units of GPU (Gas Permeation Unit, 1 GPU = 1 × 10⁻⁶). -6 cm³(STP) / (cm²・s・cmHg)). The ideal separation selectivity α is the ratio of the pure gas permeation flux of the two gases, calculated according to the reference. Each sample group was tested in parallel three times, and the arithmetic mean was taken.
[0065] Thermal stability test: The membrane samples were placed in a 180℃ high-temperature oven for continuous heat treatment for 168 hours (7 days). After cooling to 30℃, the gas permeability was tested again, and the performance retention rate after heat treatment was calculated: retention rate (%) = (performance after heat treatment / initial performance) × 100%. Each group of samples was tested in parallel 3 times, and the arithmetic mean was taken.
[0066] Long-term operational stability testing: A simulated crude helium mixture with a He / N2 / CH4 volume ratio of 5:85:10 was used and continuously operated for 500 hours at 80℃ and 0.2 MPa gauge pressure. The helium permeation flux was tested at the beginning and end of the operation, and the flux decay rate was calculated to evaluate the long-term operational stability of the membrane. Each sample was tested in triplicate, and the arithmetic mean was taken.
[0067] Morphology and structure characterization: Field emission scanning electron microscopy (FE-SEM) was used for observation.
[0068] Table 1 Performance Test Results Gas separation performance, thermal stability, and long-term operational stability were tested on the separation membranes prepared in Examples 1-3 and Comparative Examples 1-7. The results show that the present invention, through the synergistic effect of porous two-dimensional carbon nitride packing and three-step gradient fluorination process, can simultaneously improve the permeation flux, separation selectivity, and operational stability of polyimide helium separation membranes. The specific analysis is as follows: Comparing Example 1 and Comparative Example 1 (pure polyimide membrane, without filler), it can be seen that after introducing the porous two-dimensional carbon nitride nanosheets prepared by this invention, the He permeability of the membrane increased from 4.3 GPU to 11.6 GPU, an increase of 170%; the ideal selectivity of He / N2 increased from 12.5 to 42.3, an increase of 238.4%; and the ideal selectivity of He / CH4 increased from 10.8 to 38.7, an increase of 258.3%. This is because the regular nanopores within the two-dimensional carbon nitride nanosheets provide a rapid transport channel for helium, significantly increasing the permeation flux; at the same time, the two-dimensional sheets form a tortuous diffusion path in the polyimide matrix, hindering the permeation of macromolecules such as nitrogen and methane, enhancing the molecular sieving effect, and achieving a simultaneous increase in flux and selectivity.
[0069] Comparing the performance data of Example 1 with Comparative Example 2 (without ionic liquid porogen), Comparative Example 3 (without ammonium bicarbonate), and Comparative Example 4 (without both), the He / N2 selectivity of Comparative Example 2 decreased to 24.8 after the absence of ionic liquid, a decrease of 41.4% compared to Example 1. Thermal stability and long-term operational stability also significantly declined. This is because the lack of the soft template pore-forming and surface polarity regulation effects of ionic liquid reduced the in-plane pore regularity of the carbon nitride nanosheets and decreased the number of nitrogen-containing polar functional groups on the surface. This reduced the interfacial compatibility between the filler and the polyimide matrix, making it easier to generate non-selective interfacial voids, resulting in a significant decrease in separation selectivity and increased susceptibility to interfacial delamination under high-temperature operation.
[0070] In Comparative Example 3, the He permeability decreased to 8.7 GPU after the absence of ammonium bicarbonate, a 25% decrease compared to Example 1. This is because the lack of ammonium bicarbonate at low temperature decomposition and gasification has a fluffing effect on the precursor, resulting in severe particle agglomeration and interlayer stacking during thermal polycondensation. Subsequent ultrasonic exfoliation makes it difficult to obtain thin nanosheets, reduces the specific surface area and number of effective pores of the filler, decreases the rapid helium transport channels, and limits the flux improvement effect.
[0071] In Comparative Example 4, when both components were absent, the He permeability was only 5.2 GPU and the He / N2 selectivity was only 15.3, with performance close to that of a pure polyimide membrane, failing to achieve a significant performance improvement. These results indicate that the pore structure regulation and interface modification effects of ionic liquids, along with the thin-layer assisted effect of ammonium bicarbonate, are indispensable. The synergistic effect of both achieves simultaneous optimization of the packing pore structure and interfacial compatibility, jointly ensuring improved separation performance.
[0072] As can be seen from the SEM images of the fillers in Figure 3, the carbon nitride obtained in Comparative Example 3 (without ammonium bicarbonate) is mostly a blocky agglomerate with thick stacked layers, extremely low degree of layer exfoliation, no obvious two-dimensional thin-layer structure, and significantly limited specific surface area and number of in-plane pores. Although the carbon nitride obtained in Comparative Example 2 (without ionic liquid porogen) has a certain interlayer exfoliation effect, the layer structure is irregular, with severe edge stacking, failing to form a uniformly dispersed two-dimensional nanosheet structure, and the surface polarity modification is insufficient. The carbon nitride obtained in Example 1 of this invention exhibits a uniform two-dimensional thin-sheet morphology, with thin and uniformly distributed layers, no obvious large agglomerations, and fully exfoliated nanosheets with a larger specific surface area and richer, more regular in-plane pore structure.
[0073] Comparing Example 1 with Comparative Example 5 (one-step low-concentration fluorination), Comparative Example 6 (one-step medium-concentration fluorination), and Comparative Example 7 (one-step high-concentration fluorination), under the premise of the same total fluorination time, the overall performance of the three-step gradient fluorination process is significantly better than that of the one-step fluorination process: The one-step low-concentration fluorination (Comparative Example 5) was insufficient in its modification, with a He / N2 selectivity of only 34.2, a decrease of 19.1% compared to Example 1, and could not fully exert the regulatory effect of fluorination modification on free volume.
[0074] The one-step high-concentration fluorination (Comparative Example 7) reaction was too violent. The polymer chains on the membrane surface rapidly underwent deep fluorination and excessive cross-linking, forming a dense, highly fluorinated surface layer. This hindered the diffusion of fluorine gas into the membrane interior, resulting in severe unevenness in the degree of fluorination along the membrane thickness direction. At the same time, the excessive cross-linking of the surface layer caused the collapse of free volume, reducing the overall gas transport channels. Ultimately, the He permeability and separation selectivity decreased simultaneously.
[0075] The three-step gradient fluorination process of this invention reacts gradually from low concentration to high concentration, so that the degree of fluorination is evenly distributed along the film thickness direction. This ensures that the substrate is fully fluorinated to control the free volume, while avoiding structural defects caused by excessive surface fluorination. Therefore, it achieves both high permeation flux and high separation selectivity.
[0076] Example 2 uses a lower filler content and a gradient fluorination process to achieve optimal separation selectivity. Although its helium permeability is slightly higher than that of Comparative Example 3 with poor filler quality and slightly lower than that of the one-step fluorination comparative example with high filler content, its separation selectivity is significantly better than all reference samples, demonstrating the performance adjustability and high selectivity advantages of the process of this invention.
[0077] As can be seen from the data on heat treatment retention rate and long-term operation degradation rate: Examples 1-3, after heat treatment at 180℃ for 168 hours, all showed a He permeability retention rate of over 92% and a He / N2 selectivity retention rate of over 91%; after 500 hours of continuous operation, the He permeability decay rate was less than 8.5%, significantly better than all comparative examples.
[0078] Comparative samples 1, 4, and 7 showed performance retention of less than 85% after heat treatment, with long-term performance degradation exceeding 18%, and were prone to polymer plasticization, interfacial delamination, and membrane structure deterioration at high temperatures. In this invention, the two-dimensional carbon nitride nanosheets possess excellent heat resistance and mechanical reinforcement, inhibiting high-temperature plasticization and chain segment relaxation of the polyimide matrix. Simultaneously, the polar functional groups on the filler surface enhance interfacial bonding, suppressing interfacial delamination at high temperatures. The uniform fluorinated structure formed by gradient fluorination further improves the thermochemical stability of the matrix. Through the synergistic effect of these three factors, the membrane material exhibits slow performance degradation under long-term high-temperature operation, meeting the long-term continuous operation requirements of industrial scenarios such as natural gas helium extraction, syngas helium recovery, and crude helium refining.
[0079] It should be noted that the above embodiments are merely some preferred embodiments of the present invention, and not all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a highly selective, thermally stable polyimide-helium gas separation membrane, characterized in that, The preparation steps include the following: (1) Filler preparation: Two-dimensional carbon nitride nanosheets with nanoporous structures were prepared as porous fillers for the mixed matrix membrane; (2) Preparation of casting solution: Polyimide resin is dissolved in an organic solvent to obtain a homogeneous polyimide casting solution; the two-dimensional porous nanosheet filler is dispersed in an organic solvent to obtain a homogeneous filler dispersion; the filler dispersion and polyimide casting solution are mixed and stirred, and vacuum degassed to obtain a mixed casting solution; (3) Preparation of primary membrane: The mixed casting solution is coated onto the surface of the support, the solvent is evaporated by heating and vacuum dried to obtain a primary polyimide mixed matrix membrane; (4) Gradient gas phase fluorination treatment: The nascent mixed matrix membrane is placed in a gas phase fluorination reactor and treated using a three-step gradient fluorination process. After treatment, it is purged with inert gas and cooled to obtain the polyimide helium separation membrane.
2. The method for preparing the highly selective, thermally stable polyimide-helium gas separation membrane according to claim 1, characterized in that, The preparation method of two-dimensional carbon nitride nanosheets with nanoporous structure is as follows: a nitrogen-containing precursor, a halogenated 1-alkyl-3-methylimidazolium ionic liquid porogen, and ammonium bicarbonate are mixed evenly in a mass ratio of 1:(0.05~0.5):(0.1~1.0). Under an inert atmosphere, the mixture is first heated to 350~400℃ at a rate of 1~5℃ / min and held for 1~3 hours, and then heated to 500~580℃ at the same rate and held for 2~5 hours for programmed temperature-controlled thermal polycondensation. After polycondensation, the aggregates are dispersed in deionized water or ethanol, and then dispersed by ultrasonic treatment or high-speed shearing. After centrifugation and fractionation, the upper suspension is dried to obtain two-dimensional carbon nitride nanosheets with nanoporous structure.
3. The method for preparing the highly selective, thermally stable polyimide-helium gas separation membrane according to claim 2, characterized in that, The nitrogen-containing precursor is one or more of melamine, urea, or dicyandiamide, and the halogenated 1-alkyl-3-methylimidazolium ionic liquid porogen is 1-butyl-3-methylimidazolium chloride or 1-butyl-3-methylimidazolium bromide.
4. The method for preparing the highly selective, thermally stable polyimide-helium gas separation membrane according to claim 1, characterized in that, The amount of the two-dimensional porous nanosheet filler added in step (2) is 1~10wt% of the mass of the polyimide resin; the polyimide is a hexafluorodianhydride type polyimide, selected from 6FDA-ODA or 6FDA-mPDA; the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; the mass concentration of the polyimide resin in the polyimide casting solution is 10~20wt%.
5. The method for preparing the highly selective, thermally stable polyimide-helium gas separation membrane according to claim 1, characterized in that, The mass volume concentration of the homogeneous filler dispersion in step (2) is 1~10 mg / mL, and the dispersion solvent is the same as the organic solvent used in the polyimide casting solution.
6. The method for preparing the highly selective, thermally stable polyimide-helium gas separation membrane according to claim 1, characterized in that, In step (3), the method for evaporating the solvent by heating is as follows: first, evaporate at atmospheric pressure at 40~60℃ for 4~8h, then heat to 80~100℃ for 2~4h, and finally heat to 120~160℃ for vacuum drying for 12~24h to completely remove the residual solvent; the dry film thickness of the resulting nascent mixed matrix film is 20~50μm.
7. The method for preparing the highly selective, thermally stable polyimide-helium gas separation membrane according to claim 1, characterized in that, In step (4), the three-step gradient fluorination process is as follows: Step 1: low-concentration fluorination: the volume concentration of fluorine gas is 5~10 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 10~30 min; Step 2: medium-concentration fluorination: the volume concentration of fluorine gas is 15~25 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 20~40 min; Step 3: high-concentration fluorination: the volume concentration of fluorine gas is 30~40 vol%, high-purity nitrogen is used as the balance gas, the treatment temperature is 80-90℃, and the treatment time is 30~60 min.
8. The method for preparing the highly selective, thermally stable polyimide-helium gas separation membrane according to claim 7, characterized in that, The pressure inside the reactor during the entire fluorination process is 0.1~0.3MPa. After each fluorination step, the reaction gas is purged and high-purity nitrogen is introduced to purge the reactor for 10~20 minutes before proceeding to the next stage of fluorination. After all fluorination processes are completed, high-purity nitrogen is continuously introduced to purge until there is no fluorine residue in the tail gas. The membrane material is then removed after natural cooling to room temperature.
9. A highly selective, thermally stable polyimide-helium gas separation membrane, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.
